NIGERIA AND WORLD AGRICULTURAL TRADE: EFFECTS OF SAP - OLUDIMU , OLUFEMI; OSUNTOGUN, ADEWOLE (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
In discussing the major strands of policy under Nigeria's Structural Adjustment Programme (SAP), the present paper highlights the various policy measures embarked upon by government to promote agricultural export. On this front, the paper appraises the gains of SAP while drawing attention to associated 'pains'. It is concluded that if the adverse side effects of SAP could be contained, the programme represents a desirable policy option.